Pengaruh Pelayanan dan Fasilitas Terhadap Kepuasan Pasien Di RSUD Limpung Batang - Kharisma Nawang Sigit; Muhammad Syaqiq (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
This study aims to determine the effect of services and facilities on patient satisfaction in Limpung Batang Hospital. The poppulation in this study were all people who had been patients, both outpatients and inpatients. The sammpling technique in this study ussed the accidental sampling method, the researchers took samples that happened to be met at that time there were 50 patients who met the sample selection criteria. The data analysiss technique used in this ressearch is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test. The ressults showed that the service variable partially affected patient satisfaction with the value and the facility variable partially affected patient satisfaction. Service and facility variables simultaneously affect patient satisfaction in Limpung Batang Hospital. Keywords: Services, facilities, patient satisfaction